2010
DOI: 10.1007/s00421-010-1471-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upper-limb exercise on lower-limb cutaneous microvascular function in post-surgical varicose-vein patients

Abstract: important factor in optimal exercise prescription for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…P-values less than 0.05 were considered statistically significant, while the sample size calculation was undertaken based on our previous work. 7 From Table II we observe that, following exercise, the average width of the multifractal spectra in both lower leg and forearm does not vary significantly before and after last dose of iontophoresis (see cases 1 and 2). Moreover, for forearm, the average width of the multifractal spectra before exercise does not change significantly prior to iontophoresis compared to that after last dose of iontophoresis (see case 3 in Table II).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…P-values less than 0.05 were considered statistically significant, while the sample size calculation was undertaken based on our previous work. 7 From Table II we observe that, following exercise, the average width of the multifractal spectra in both lower leg and forearm does not vary significantly before and after last dose of iontophoresis (see cases 1 and 2). Moreover, for forearm, the average width of the multifractal spectra before exercise does not change significantly prior to iontophoresis compared to that after last dose of iontophoresis (see case 3 in Table II).…”
Section: Resultsmentioning
confidence: 86%
“…It is important, however, to note that our results should not be generalized, and that these findings may only be true for the older, untrained but healthy population that we studied and for the type of exercise that we have chosen for this study. Our previous work, where contradictory findings were observed on the effect of exercise in different populations (see, for example, differences between a patient group in Klonizakis et al 7 and a normal population in Klonizakis and Winter 5 on armcranking exercise), should make us very cautious on their interpretation; indeed, different compensatory mechanisms to preserve heat-induced vasodilatory responses have been suggested for different age-groups by others. 9 It is, therefore, worth undertaking similar studies in clinical populations, different age-groups, and with other forms of exercise to explore the role of NO in the observed changes of perfusion or cutaneous vascular conductance quantities.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous work has shown that lower-limb resistance training can improve calf muscle pump function, ankle range of motion and lower-limb haemodynamics in people with venous ulceration (Kan and Delis 2001 ; Jull et al 2009 ; O’Brien et al 2013 ). Our group has also demonstrated that lower-limb endurance training (Klonizakis et al 2009 ), but not upper-limb endurance training (Klonizakis et al 2010 ), can improve lower-limb cutaneous microvascular reactivity in people who had recently had surgery for varicose veins. However, a recent systematic review concluded that further research is required to determine whether exercise training has a beneficial effect on ulcer healing and health-related quality of life (Yim et al 2015 ).…”
Section: Introductionmentioning
confidence: 80%